1996
DOI: 10.1007/bf01273152
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT1A receptor antagonist (S)-UH-301 decreases dopamine release in the rat nucleus accumbens and striatum

Abstract: In this study we employed in vivo microdialysis to examine the effects of the selective 5-HT1A receptor antagonist (S)-5-fluoro-8-hydroxy-2-(dipropylamino)tetralin [(S)-UH-301] on extracellular concentrations of dopamine (DA) and its metabolites dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA) in the nucleus accumbens (NAC) and dorsal striatum of awake freely moving rats. Systemic administration of (S)-UH-301 (1.25, 2.5, 5.0 mg/kg s.c.) dose-dependently decreased extracellular concentrations of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Since psilocybin also acts upon 5-HT 1A receptors (Buckholtz et al 1990;McKenna et al 1990) and stimulation of 5-HT 1A autoreceptors is expected to enhance the dopaminergic tone (Neal-Beeliveau et al 1993), one might speculate that psilocybin increases striatal dopamine release through a concomitant stimulation of both 5-HT 1A and 5-HT 2A receptors. This hypothesis is supported by the finding that 5-HT 1A agonists can facilitate dopamine release in the striatum and nucleus accumbens (Benloucif and Galloway 1991), while 5-HT 1A antagonist have been reported to inhibit dopamine release in these brain regions (Parson and Justice 1993;Boulenguez et al 1996;Nomikos et al 1996). Furthermore, recent studies in rats demonstrated that the changes in locomotor activity produced by the 5-HT 1A agonist 8-OH-DPAT (Hillegaart et al 1995) or the classic indolehallucinogen LSD were attenuated by pretreatment with the selective 5-HT 1A antagonist WAY-100,635 (Sipes and Geyer 1995;Krebs-Thomson and Geyer 1996).…”
Section: Discussionmentioning
confidence: 80%
“…Since psilocybin also acts upon 5-HT 1A receptors (Buckholtz et al 1990;McKenna et al 1990) and stimulation of 5-HT 1A autoreceptors is expected to enhance the dopaminergic tone (Neal-Beeliveau et al 1993), one might speculate that psilocybin increases striatal dopamine release through a concomitant stimulation of both 5-HT 1A and 5-HT 2A receptors. This hypothesis is supported by the finding that 5-HT 1A agonists can facilitate dopamine release in the striatum and nucleus accumbens (Benloucif and Galloway 1991), while 5-HT 1A antagonist have been reported to inhibit dopamine release in these brain regions (Parson and Justice 1993;Boulenguez et al 1996;Nomikos et al 1996). Furthermore, recent studies in rats demonstrated that the changes in locomotor activity produced by the 5-HT 1A agonist 8-OH-DPAT (Hillegaart et al 1995) or the classic indolehallucinogen LSD were attenuated by pretreatment with the selective 5-HT 1A antagonist WAY-100,635 (Sipes and Geyer 1995;Krebs-Thomson and Geyer 1996).…”
Section: Discussionmentioning
confidence: 80%
“…It could be postulated that an overflow technique such as microdialysis simply lacks the sensitivity to measure small changes in 5-HT, and increases in synaptic 5-HT are sufficient to mediate the observed acute anxiolytic effect. Alternatively, SSRIs and 5-HT 1A/B receptor antagonists have been shown to modulate several other neurotransmitter systems including glutamate (Marcoli et al, 1999;Schechter et al, 2002), acetylcholine (Consolo et al, 1996;Nakai et al, 1998;Koyama et al, 1999), dopamine (Boulenguez et al, 1996;Nomikos et al, 1996;Iyer and Bradberry, 1996), and noradrenaline (Hajos-Korcsok et al, 1999) which may contribute to or mediate the SB-649915-B-induced effect. However, the studies to address the effects on systems other than the 5-HT and monoaminergic (Hughes et al, 2007), have, as yet, not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…It was also proposed from in vivo experiments in rats that stimulation of DA release involves the activation of 5-HT 1 , 5-HT 3 and/or 5-HT 4 receptors in the striatum (Benloucif et al 1993). The participation of 5-HT 1A receptors was suggested by the fact that local infusion of the selective 5-HT 1A receptor antagonist (S)-UH-301 in awake freely moving rats decreased DA release in the nucleus accumbens and dorsal striatum (Nomikos et al 1996). Moreover, local administration of a selective serotonin reuptake inhibitor (SSRI) facilitated release of DA in the corpus striatum (Yadid et al 1994).…”
Section: Introductionmentioning
confidence: 99%